Karakteristik Marketing Shariah dalam Keputusan Menjadi Nasabah Perbankan Shariah - Didin Burhanuddin Rabbani (STAIFAS-Press, 2017)
AbstractThis research was conducted to know and analyze the influence of shará¿‘'ah marketing characteristic in the decision to become shar'ah banking customer (research on student of Faculty of Economics and Islamic Business UIN Sunan Kalijaga Yogyakarta), where in marketing characteristic shar''ah consist of four indicators namely, theistic (rabbÄniyah), ethical (akhlÄqiyah), realistic (al-waqi'iyyah), and humanistic (al-insaniyah) that will be measured for influence on the decision to become a customer. The method used in this research using quantitative approach, the data used is the primary data by distributing questionnaires to a number of respondents who have taken into account the level of trust. Based on the results of data analysis that has been collected, it is evident that the characteristics of marketing shará¿‘'ah influence in the decision to become shará¿‘'ah banking customers (a research of students of the Faculty of Economics and Islamic Business UIN Sunan Kalijaga Yogyakarta) is very weak, among four indicators of marketing characteristics shará¿‘'ah above, ethical (akhlÄqiyah) is the only one influencing the decision to become a shará¿‘'ah banking customer. The conclusion that the academics and students in the environment of the object of research should instill a love attitude to shará¿‘'ah banking, so that shará¿‘'ah banking can also be loved by the community and to support the growth of shará¿‘'ah banking in Indonesia.Keywords: shará¿‘'ah marketing characteristics; theistic; ethical; realistic, humanistic, customer decisions, shar'ah banking.Falasifa: Jurnal Studi KeislamanVolume 08,